2002
DOI: 10.1128/aem.68.7.3243-3250.2002
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Bacterial Community Composition by Oligonucleotide Fingerprinting of rRNA Genes

Abstract: One of the first steps in characterizing an ecosystem is to describe the organisms inhabiting it. For microbial studies, experimental limitations have hindered the ability to depict diverse communities. Here we describe oligonucleotide fingerprinting of rRNA genes (OFRG), a method that permits identification of arrayed rRNA genes (rDNA) through a series of hybridization experiments using small DNA probes. To demonstrate this strategy, we examined the bacteria inhabiting two different soils. Analysis of 1,536 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
70
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
5
5

Relationship

2
8

Authors

Journals

citations
Cited by 120 publications
(77 citation statements)
references
References 34 publications
6
70
0
1
Order By: Relevance
“…Similar results were observed by other authors (e.g. Sessitsch et al, 2001;Valinsky et al, 2002;Sun et al, 2004;Toyota and Kuninaga, 2006) where variations in the composition of bacterial community also depended on the soil type, sample origin and plant growth stage. Smit et al (2001) suggested that the ratio between Proteobacteria and Acidobacteria frequency can be indicative of the soil nutrient status when calculated as % Proteobacteria/(sum of % Proteobacteria and % Acidobacteria).…”
Section: Introductionsupporting
confidence: 91%
“…Similar results were observed by other authors (e.g. Sessitsch et al, 2001;Valinsky et al, 2002;Sun et al, 2004;Toyota and Kuninaga, 2006) where variations in the composition of bacterial community also depended on the soil type, sample origin and plant growth stage. Smit et al (2001) suggested that the ratio between Proteobacteria and Acidobacteria frequency can be indicative of the soil nutrient status when calculated as % Proteobacteria/(sum of % Proteobacteria and % Acidobacteria).…”
Section: Introductionsupporting
confidence: 91%
“…DNA was purified and analyzed from all five initial isolates. As a result of this analysis, the sequence was assigned to the Enterobacter genus 16) , and specifically to sequence S000544285, which belongs to Enterobacter hormaechei 17) .…”
Section: Cultivation Of Clinical Isolates From Atheromatous Tissue Anmentioning
confidence: 99%
“…While T-RFLP does often yield a higher number of OTUs when compared to DGGE, the disadvantage is that the PCR amplicons cannot be recovered and, hence, used to obtain taxonomic or phylogenetic information about the microbial community. While the above mentioned genetic fingerprinting techniques permit rapid analysis of numerous samples, they generate only superficial descriptions of microbial community compositions (Valinsky et al 2002).…”
Section: Terminal Restriction Fragment Length Polymorphismmentioning
confidence: 99%